COMPETENCY OF ENTREPRENEURSHIP AND PERFORMANCE OF PRINCIPAL IN ELEMENTARY SCHOOL - Muhammad Yogi Riyantama Isjoni (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
Based on the facts that occur in the field the performance problem of principals is still not effective because it shows the phenomenon that the low competency of principals about entrepreneurship The author is interested in examining more deeply by researching the performance of elementary school principals in Peranap District, Indragiri Hulu Regency in terms of entrepreneurial competence. This study aims to reveal how much influence entrepreneurial competence has on the performance of elementary school principals in Peranap District, Indragiri Hulu District. The method used in this study is a causal method with quantitative research. Data is taken from the distribution of instruments to 34 public elementary school principals from Peranap District, Indragiri Hulu Regency. The results showed that: There was a significant effect between entrepreneurial competence (X) on the Principal's Performance (Y) with a correlation coefficient ry = 0.343 and a regression equation = 71,301 + 0.463X. The conclusion of this study is entrepreneurial competence in the performance of school principals produces a correlation coefficient of 0.586 and contributes 34.3% to the performance of school principals. The contribution of this entrepreneurial competency variable provides evidence that entrepreneurial competence is one of the determinants of school principal performance. This study recommends that the principals' entrepreneurial competence needs to be improved to improve the performance of the principal, efforts can be made to create a happy feeling and a comfortable school environment and the principal involves all teachers to work actively in achieving the vision, mission and goals of the school